Investigation on fault-tolerant optical multicast networks - Yan, Yuanyuan (2012)
The preconfigured protection cycle (p-cycle) proposed by Grover and Stamatelakis [1] is able to achieve ring like restoration speed and mesh like efficiency in optical fiber communication networks. With the advancement of technology, the demand for multicast networks increases dramatically, which requires more attention to be paid to the multicast network protection.